MOLECULAR DETECTION OF PARVOVIRUS FROM SERA OF CHILDREN WITH RASH RED ILLNESS (World Bulletin of Public Health, 2022)
A parvovirus infection is distinguished by a bright red rash on the cheeks. Human parvovirus B19 infection is a typical and contagious illness in children.
Keywords: Rash; parvovirus; B19; gender